A Study on the Tracking Problem in Vehicular Ad Hoc Networks - Xing Zhang; Bang Liu; Jinchuan Tang (International Journal of Distributed Sensor Networks, 2013)
Vehicles have the characteristic of high mobility which makes vehicular ad hoc networks (VANETs) different from other mobile ad hoc networks (MANETs), it is more difficult to establish an end-to-end route in VANETs, and the source and destination nodes keep moving fast from their original locations. To guarantee a data packet will finally be received by the destination node in VANETs, and the location of the destination node must be tracked constantly. Advanced Greedy Forwarding (AGF (Naumov et al. (2006))) is a good way to estimate the location of the destination node by taking advantage of the velocity vectors; however, a vehicle changes its velocity constantly, it would be very inaccurate to estimate the location of a vehicle via its initial velocity. In this paper, we study the tracking problem in VANETs and propose two solutions: area-based tracking (ABT) and parked vehicle-assisted tracking (PVAT). ABT works well when the delays in data transmission from source to destination are small, and PVAT works as a supplement of ABT and deals with the situation of which the delays are large. PVAT takes advantage of vehicular sensors to detect whether a vehicle is parking. Simulations show better results compared to AGF.